Reologia de farinha integral para biscoitos enriquecida com diferentes fontes proteicas - Massad, Janaina Aronne (2021)
The biscuit is a product accepted and consumed by several individuals, of any age and has a high attractive power, especially for children and elderly. When there is a partial replacement of wheat flour by other proteins in the formulation of bakery products, some technological and rheological characteristics of the mixtures are affected, causing losses of processability and/or sensory to the elaborated products. The general objective of the work was to develop a mixture of whole wheat flour enriched with proteins (soy isolate (PS), whey (PSL) and/or pea isolate (PE)), for molded biscuits. The rheology of the mass was evaluated in the Mixolab® equipment. In relation to the water absorption parameter, it was observed that the lowest levels of water absorption were found with mixtures containing PSL, the lower the higher the proportion of PSL in the mixture. This result compromised the development time of the mass, since the mixtures containing higher levels of PSL showed longer development times, unlike samples containing PE and PS, which showed development times closer to that observed for the control sample (100 % of whole wheat flour). The formulations with whey protein (PSL) (100%) and the binary mixtures of PSL with PE were the ones that presented the highest mixture stability. In relation to the Amplitude, it was observed that the mixtures containing PE and PSL were closer to the control sample region. The model for parameter C1 showed a low coefficient of determination, indicating that the model cannot explain the influence of mixtures on this variable. Blends containing pea protein and whey are the most promising for increasing the C2 parameter, since, during processing, they form a gel that compensates the weakening of gluten matrix exposed to heating. In general, the presence of external proteins promoted competition with the gluten protein for water, resulting in damage to the formation of the gluten matrix, and affecting the Stability. On the other hand, pea protein and whey had a positive influence over the mixture Amplitude. The optimal mixture for molded biscuits was obtained applying desirability function and resulted in 75% whole wheat flour, 18.75% PE and 6.25% PSL. Comparing with the protein content of pure whole wheat flour (12.75 ± 0.4%), the optimized formulation showed an increase by 64% in protein content, representing an interesting contribution at the consumer level, and, it can be considered that the optimized mixture is enriched with proteins.